Numbers and meanings. Ideality in the incipient Husserl’s phenomenology - Chillón, José Manuel (Anales del Seminario de Historia de la Filosofía, 2017)
The reflection on numbers and meanings are a good example of how the incipient phenomenology is in the realm of pure logic. The paper states that, due to ambiguities in these early works and in order to draw a reflection that does not tear the philosophical personality of Husserl, the thesis of the ideality be read from the perspective of later works. This paper reconstructs, from initial analysis of the numbers and meanings, the thesis of the ideality Husserl which, in our view, detect the fundamental aspects of phenomenology despite the subsequent abandonment of the eidetic realism.